Three-dimensional reconstruction and segmentation of intact Drosophila by ultramicroscopy - Jährling, Nina; Becker, Klaus; Schönbauer, Cornelia; Schnorrer, Frank; Dodt, Hans-Ulrich (Frontiers in Systems Neuroscience, 2010)
Genetic mutants are invaluable for understanding the development, physiology and behaviour of Drosophila. Modern molecular genetic techniques enable the rapid generation of large numbers of different mutants. To phenotype these mutants sophisticated microscopy techniques are required, ideally allowing the 3D-reconstruction of the anatomy of an adult fly from a single scan. Ultramicroscopy enables up to cm fields of view, whilst providing micron resolution. In this paper, we present ultramicroscopy reconstructions of the flight musculature, the nervous system, and the digestive tract of entire, chemically cleared, drosophila in autofluorescent light. The 3D-reconstructions thus obtained verify that the anatomy of a whole fly, including the filigree spatial organisation of the direct flight muscles, can be analyzed from a single ultramicroscopy reconstruction. The recording procedure, including 3D-reconstruction using standard software, takes no longer than 30 minutes. Additionally, image segmentation, which would allow for further quantitative analysis, was performed.